Parental Involvement in the Implementation of CBC in Primary Schools - Kadau, Ibrahimu (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
This study investigated challenges impeding parental involvement in implementing the Competence-Based Curriculum (CBC) in Tanga, Tanzania. Purposive sampling used to recruit six participants in interviews which were conducted in Kiswahili language. The obtained data were translated to English language and were analyzed by using thematic analysis. It was found that, despite of, recent improvements in PI, there have been persistent factors contribute to ineffective PI. The challenges includes; limited parental awareness, conflicting work schedules, economic constraints, perceived incompetence, and negligence. To enhance parental involvement, the study recommends that, with fee-free education initiatives, the government should consider both curricular and extracurricular programs which are the key to effective PI in CBC implementation. Beside, parents and school should consider the presence of dual responsibilities of parents in curriculum implementation.